Exploring the diversity of alfalfa within Brazil for tropical production - Santos, Iara Gonçalves dos; Rocha, João Romero do Amaral Santos de Carvalho; Vigna, Bianca Baccili Zanoto; Cruz, Cosme Damião; Ferreira, Reinaldo de Paula; Basigalup, Daniel Horacio; Marchini, Renato Maldigamm Scorsolini (Springer, 2021)
Alfalfa (Medicago sativa L.) is a forage legume of great interest because of its role in milk production schemes. Although it has the potential to be cultivated in different edaphoclimatic regions, the fodder production in tropical regions is limited. The objectives of this study were to perform phenotypic and molecular characterization of alfalfa germplasm, to examine the relationship between dissimilarity based on phenotypic and molecular information and to identify the germplasm with potential to generate base populations adapted to tropical conditions. The genetic values of nine traits from seventy-seven alfalfa accessions of a genetic background amenable to a temperate climate were obtained to characterize phenotypic diversity, and microsatellite markers were used to assess molecular diversity. Phenotypic information based on joint deviance analysis revealed the presence of genetic diversity. The correlation between the dissimilarity matrices of genetic values and molecular data was low. Based on phenotypic and molecular data, a great base population would be composed of Pro INTA Patricia, Pro INTA Super Monarca, Mecha, Magna 601, WL 525, ACA 900, Bacana, CUF 101, Crioula, and Ruano. These populations have at least 50 distinct parents, presented high dry matter yield, besides favorable alleles for regrowth ability, biomass yield, and persistence. The genetic variability observed for most traits indicates a high potential for the development of alfalfa base populations adapted to the tropical condition. Once adapted synthetic alfalfa populations are selected, they may be integrated into breeding programs in other tropical regions of the world.